7(3x-1)=5+4(x-3)

Simple and best practice solution for 7(3x-1)=5+4(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3x-1)=5+4(x-3) equation:


Simplifying
7(3x + -1) = 5 + 4(x + -3)

Reorder the terms:
7(-1 + 3x) = 5 + 4(x + -3)
(-1 * 7 + 3x * 7) = 5 + 4(x + -3)
(-7 + 21x) = 5 + 4(x + -3)

Reorder the terms:
-7 + 21x = 5 + 4(-3 + x)
-7 + 21x = 5 + (-3 * 4 + x * 4)
-7 + 21x = 5 + (-12 + 4x)

Combine like terms: 5 + -12 = -7
-7 + 21x = -7 + 4x

Add '7' to each side of the equation.
-7 + 7 + 21x = -7 + 7 + 4x

Combine like terms: -7 + 7 = 0
0 + 21x = -7 + 7 + 4x
21x = -7 + 7 + 4x

Combine like terms: -7 + 7 = 0
21x = 0 + 4x
21x = 4x

Solving
21x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
21x + -4x = 4x + -4x

Combine like terms: 21x + -4x = 17x
17x = 4x + -4x

Combine like terms: 4x + -4x = 0
17x = 0

Divide each side by '17'.
x = 0

Simplifying
x = 0

See similar equations:

| -4k-8+11=-3k-12 | | -16x=-8 | | 3x^2+12x-61=0 | | 3x^2+36+105= | | -7+4(3a+1)=-7 | | 8+7x=109 | | 6/5+3/5x=61/30+7/6x+1/6 | | -7x-9y=-3 | | 1/6(6y+12)-9=-1/4(12y-20) | | 7=2x/5 | | 3x+6-x=69 | | 89-(5x+13)=5(x+2)+x | | 5d-2(6d+5)=5-(10+10d) | | 3-2lnx=8 | | -113=7+10x | | 7/6x+3x/5 | | 34=16*x-14 | | 6(3+2x)-1=65 | | a+(b^2)*3c-2d= | | (9ab+7cd)*3e= | | r+0.10=760 | | 9ab+7cd= | | 30=-5/4x | | m=19-5(x-n) | | 5a+4b+3c+4d+3e= | | 5a*4b*3c*4d*3e= | | r/2+0.6r=247 | | 2a-3b=12 | | 8-2(t-1)=t+7 | | 5a*4b*3c= | | 7/5+8/3d | | 7=(3x+9)+7 |

Equations solver categories